A genetic screen for dominant chloroplast reactive oxygen species signaling mutants reveals life stage-specific singlet oxygen signaling networks - Matthew D. Lemke; Jesse D. Woodson (Frontiers in Plant Science, 2024)
IntroductionPlants employ intricate molecular mechanisms to respond to abiotic stresses, which often lead to the accumulation of reactive oxygen species (ROS) within organelles such as chloroplasts. Such ROS can produce stress signals that regulate cellular response mechanisms. One ROS, singlet oxygen (1O2), is predominantly produced in the chloroplast during photosynthesis and can trigger chloroplast degradation, programmed cell death (PCD), and retrograde (organelle-to-nucleus) signaling. However, little is known about the molecular mechanisms involved in these signaling pathways or how many different signaling 1O2 pathways may exist.MethodsThe Arabidopsis thaliana plastid ferrochelatase two (fc2) mutant conditionally accumulates chloroplast 1O2, making fc2 a valuable genetic system for studying chloroplast 1O2-initiated signaling. Here, we have used activation tagging in a new forward genetic screen to identify eight dominant fc2 activation-tagged (fas) mutations that suppress chloroplast 1O2-initiated PCD.ResultsWhile 1O2-triggered PCD is blocked in all fc2 fas mutants in the adult stage, such cellular degradation in the seedling stage is blocked in only two mutants. This differential blocking of PCD suggests that life-stage-specific 1O2-response pathways exist. In addition to PCD, fas mutations generally reduce 1O2-induced retrograde signals. Furthermore, fas mutants have enhanced tolerance to excess light, a natural mechanism to produce chloroplast 1O2. However, general abiotic stress tolerance was only observed in one fc2 fas mutant (fc2 fas2). Together, this suggests that plants can employ general stress tolerance mechanisms to overcome 1O2 production but that this screen was mostly specific to 1O2 signaling. We also observed that salicylic acid (SA) and jasmonate (JA) stress hormone response marker genes were induced in 1O2-stressed fc2 and generally reduced by fas mutations, suggesting that SA and JA signaling is correlated with active 1O2 signaling and PCD.DiscussionTogether, this work highlights the complexity of 1O2 signaling by demonstrating that multiple pathways may exist and introduces a suite of new 1O2 signaling mutants to investigate the mechanisms controlling chloroplast-initiated degradation, PCD, and retrograde signaling.